2018
DOI: 10.7567/jjap.57.06hj10
|View full text |Cite
|
Sign up to set email alerts
|

New local joining technique for metal materials using exothermic heat of Al/Ni multilayer powder

Abstract: The use of Al/Ni multilayer powders as a new heat source has been expected for metal joining technique owing to their instantaneous reaction and enormous amount of exothermic heat. In this study, the effects of the amount of Al/Ni multilayer powders on the electrical and mechanical properties of the joining part of Al strip specimens were examined. These electrical and mechanical properties were estimated by electric resistivity measurement using the four-terminal method and shear test, respectively. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In the experiment, the DC power supply was set to a maximum of 10 V and 1 A. [28][29][30] Tests were all conducted in laboratory air. A non-contact thermometer (FT-H40K) was used to measure exothermic surface temperatures.…”
Section: Exothermic Performance Test Of Titanium-silica Nanoparticlesmentioning
confidence: 99%
“…In the experiment, the DC power supply was set to a maximum of 10 V and 1 A. [28][29][30] Tests were all conducted in laboratory air. A non-contact thermometer (FT-H40K) was used to measure exothermic surface temperatures.…”
Section: Exothermic Performance Test Of Titanium-silica Nanoparticlesmentioning
confidence: 99%
“…In our study, to improve the productivity and convenience of the heat source, an Al/Ni multilayer powder fabricated by the coldrolling and frictional pulverizing methods was developed, and the thermal reaction characteristics were studied. 13,[25][26][27][28] In a previous study, we revealed that the exothermic reaction characteristics, such as the reaction speed and maximum exothermic reaction temperature, increase with an increase in the number of cold-rolling passes. 25) These characteristics can be controlled to some extent by changing the rolling conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The exothermic characteristics of Al/Ni multilayer powders have also been examined. [26][27][28] It was found that such characteristics (e.g. maximum temperature, reaction rate, and intermetallic compound production) can be controlled by changing the number of rolling passes.…”
Section: Introductionmentioning
confidence: 99%